2023
DOI: 10.1039/d2cp05044g
|View full text |Cite
|
Sign up to set email alerts
|

How do salt and lipids affect conformational dynamics of Aβ42 monomers in water?

Abstract: It is well established that amyloid β-protein (Aβ) self-assembly is involved in triggering of Alzheimer’s disease. On the other hand, evidence of physiological function of Aβ interacting with lipids has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
(168 reference statements)
1
5
0
Order By: Relevance
“… Overall, our prior work demonstrated that CHARMM36m performs better than OPLS-AA/M and Amber ff14SB in several aspects of conformational dynamics. Consistent with these observation, we applied CHARMM36m simulations to examine conformational ensembles of polyarginine peptides . It is also worth noting that CHARMM36m is routinely used to examine dynamics of one of the most notorious intrinsically disordered proteins, amyloid β-protein (Aβ), and its interactions with lipids , because it outperforms other MD force fields when modeling peptide self-assembly …”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“… Overall, our prior work demonstrated that CHARMM36m performs better than OPLS-AA/M and Amber ff14SB in several aspects of conformational dynamics. Consistent with these observation, we applied CHARMM36m simulations to examine conformational ensembles of polyarginine peptides . It is also worth noting that CHARMM36m is routinely used to examine dynamics of one of the most notorious intrinsically disordered proteins, amyloid β-protein (Aβ), and its interactions with lipids , because it outperforms other MD force fields when modeling peptide self-assembly …”
Section: Resultsmentioning
confidence: 60%
“…63−66 Consistent with these observation, we applied CHARMM36m simulations to examine conformational ensembles of polyarginine peptides. 11 It is also worth noting that CHARMM36m is routinely used to examine dynamics of one of the most notorious intrinsically disordered proteins, amyloid β-protein (Aβ), and its interactions with lipids 67,68 because it outperforms other MD force fields when modeling peptide self-assembly. 69 Using the above rationale, we examined the two linear motifs using CHARMM36m/TIP3P and Amber ff14SB/TIP4P-2005 simulations (see Materials and Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…These time scales are far removed from those available to the computational community. The oligomeric state also affects the propensity to insert into membranes . Monomers and dimers are less likely to insert than higher oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this depends on the question being asked. If one aims to thoroughly characterize a well-established native state or a disordered system, , multiple shorter simulations seem preferable. However, if one wants to see if a pore collapses and this collapse takes, say, 10 μs, doing 100 simulations of 100 ns each will not be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation